(untitled) (Bangladesh Journal of Urology, 2026)
Background: Female urethral stricture (FUS) is a rare, underdiagnosed condition often misidentified as other lower urinary tract disorders due to nonspecific symptoms. Although traditionally considered uncommon in women, recent studies indicate higher prevalence, often linked to trauma, infections, or iatrogenic causes. Conservative treatments like dilation offer temporary relief with high recurrence. Buccal mucosa graft (BMG) urethroplasty, especially the dorsal onlay technique, has shown superior, durable outcomes due to its favorable tissue properties and anatomical advantages. Aim of the study: This study aims to evaluate the clinical outcome of dorsal onlay BMG urethroplasty in female patients with urethral stricture treated at a tertiary-level hospital in Bangladesh. Methods: This prospective observational study was conducted in the Urology Department of a tertiary hospital in Bangladesh over a defined period 2 years, from 1st January 2022 to 31st December 2023, to assess dorsal onlay buccal mucosa graft (BMG) urethroplasty outcomes in 30 female patients with urethral stricture. Patients included were aged 18–65 years, refractory to dilatation, and diagnosed using uroflowmetry, urethroscopy, or VCUG. Exclusions were active infection, malignancy, neurogenic bladder, or poor surgical fitness. All underwent standardized preoperative evaluation and BMG urethroplasty under general anesthesia. Postoperative follow-up at 1, 3, 6, and 12 months assessed symptom relief and uroflowmetry. Data were analyzed using SPSS version 26.0. Results: The study included 30 female patients with a mean age of 42.6±9.2 years and a BMI of 25.3±3.1 kg/m². Most were married (83.3%) and from urban areas (63.3%). Poor urinary stream (90%) was the most common symptom, followed by urgency/frequency (66.7%) and UTIs (56.7%). The average symptom duration was 14.2±6.7 months, with 3.1±1.6 prior dilatations. Strictures averaged 1.4±0.6 cm in length, most commonly in the mid-urethra. Postoperatively, Qmax improved from 5.2 to 18.4 ml/sec, and PVR decreased from 86.5 to 18.6 ml. Complete symptom relief occurred in 80% of cases, with minimal complications, confirming the procedure’s effectiveness and safety. Conclusion: Dorsal onlay buccal mucosa graft urethroplasty is a safe, effective option for treating female urethral stricture. It offers high success rates, sustained symptom relief, and low complication rates. The study advocates the broader use of reconstructive surgery over repeated dilatation, especially in resource-limited settings, to improve patient outcomes and quality of life. Bangladesh J. Urol. 2025; 28(2): 54-59